Knowledge, attitude and practices of women towards vaginal discharge - Varghese, Shiny; Kour, Gagandeep; Chacko, Joffi; Rathi, Juhi; Dhar, Tapasya (International Journal of Advances in Medicine, 2017)
Background: Vaginal discharge (VD) is one of the common problems affecting the reproductive life of women which has high prevalence in South-East Asia. The aim was to analyse the knowledge, attitude and perception of women towards vaginal discharge (VD). Methods: A prospective study was conducted on 150 women, above 18 years of age, irrespective of marital status, who presented with VD and its associated symptoms in the Out Patient Department, Obstetrics and Gynaecology, Christian Medical College and Hospital, Ludhiana, India. The study involved a period from April 2015 to June 2016. A pre-structured questionnaire was used to record various parameters related to VD. Results: Results of the present study revealed a relationship between the symptoms of VD and various socio-cultural based beliefs. Opinions regarding various aetiological factors and perception of preventive measures were recorded. Conclusions: A direct relationship between knowledge attitude and perception about symptoms of VD and educational status of the patients was observed. The study emphasised the need to take effective measures to educate women about reproductive health at community level.